The Use of Google Classroom in Learning Writing: A Study of EFL Students’ Attitude (Program Studi Pendidikan Teknologi Infromasi UMK, 2024)
This study is aimed to determine EFL student attitudes towards the use of Google Classroom in writing. It was conducted at the SMPN 14 Kendari. This study's participants are four students from class IX2. Purposive sampling was used to choose study participants depending on the criteria required by the researcher. The design of this study was based on case study methods. Data collection was done through an interview. The results showed that there were five student affective attitudes toward using Google Classroom in writing, namely: 1). Usefulness: students can write sentences in English in Google Classroom, but students cannot write sentences in English in Google Classroom. 2) ease of use: students find it easy to do writing assignments in English in Google Classroom; 3) accessability: students feel the process of learning in Google Classroom is easily accessible, and students find the learning process in Google Classroom difficult to access. 4) Engagement: students are actively engaged in the writing process when using Google Classroom, as it provides interactive features and tools that enhance their learning experience. Additionally, students may feel less motivated to participate in writing activities if they encounter technical difficulties or limitations within the platform. 5) Collaboration: Google Classroom allows for seamless collaboration among students, enabling them to work together on writing assignments and provide feedback to one another. However, some students may struggle with collaborative tasks or feel hesitant to share their work with peers.